Māori exercise professionals: Using Indigenous knowledge to connect the space between performance and wellbeing. Issue 1 (2nd January 2023) - Muriwai, Emerald; Manuela, Sam; Cartwright, Claire; Rowe, Luke
Abstract: Indigenous voices and perspectives are necessary in advancing applied and global sport psychology. In Aotearoa New Zealand, Māori sport and exercise professionals are thriving despite existing systems that devalue, discriminate and exclude Māori from fulfilling their potential. This qualitative study investigated the perspectives of ten Māori sport and exercise experts including academics, allied health professionals, athletes, coaches and Māori healers in order to develop a critical understanding of their work related experiences and analyze the diverse forms of knowledge on which they draw. Participants-collaborators were interviewed using an insider research design to facilitate discussion about their current work. Results support a "space between" model and suggest that Māori sport and exercise work enables excellence in sport performance while also meeting holistic wellbeing needs of communities. Māori exercise professionals identified that their presence in their respective fields "speaks back" to racist practices and entrenched barriers that colonize Māori success. Further, applying holistic notions of wellbeing and ancestral knowledge to sport and exercise was seen as default and ordinary; shifting the illusion that sport and exercise operates in a culture-less, timeless and physical vacuum. From an applied and Indigenous perspective, these results emphasize that Indigenous sport leadership and practices are unequaled by Western methods and science alone. Māori exercise professionals demonstrate cultural innovation and intersectionality that not only revolutionizes sport, but brings with it essential community wellbeing. Lay summary: This article explores the experiences of ten Māori exercise professionals and analyses the diverse forms of knowledge they draw on in their work. The study provides insight into how Māori exercise professionals utilize their knowledge of social contexts and culture, in turn expanding the scope of sport and exercise psychology.